Judicial Process and Medical Practice Dispute Resolution in Thailand - Saengpuang, Kantapong; Umpai, Kiarttiphorn (Rajapark Journal, 2021)
There has been attempts to implement a no-fault compensation system from abroad into the Thai legal system. However, the existing method does not effectively solve the existing problem. The research on guidelines for legal implementation on medical practice by exercising the alternative dispute resolution in Thailand, therefore, aimed to study the mistakes and possible disputes in medical practice. The research discussed the laws of Thailand and those of other jurisdictions on both substantive laws and alternative dispute resolutions. The methodology of this research was a qualitative by documentary research, i.e., textbooks, legal and medical articles, and primary and secondary information from the internet. The result of the research indicated that such system exists under Section 41 of The National Health Security Act, B.E. 2545 (A.D. 2002) and Section 63 (7) of The Social Security Act, B.E. 2533 (A.D. 1990). Although, the scope of the legal enforcement of both legislations cannot compensate everyone equally which is against the objective of the laws themselves. This research, thus, suggests the following enactment and amendment of the following laws. Firstly, specific legislation should be enacted The Patient Compensation for Injury from Medical Practice Proposed Act. Secondly, Section 17 on the objective of compensation fund, Section 18 on subsidy to private medical institutions, and Section 19 on finance on the subsidy, including other related laws.